(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Alcohol intoxication remains a major etiological factor contributing to structural and functional impairment of the pancreas due to its high sensitivity to toxic influences. Morphological and morphometric evaluation is essential for understanding the degree of tissue damage and adaptive changes under toxic conditions. Objective: To perform a comparative analysis of morphological and morphometric changes in the pancreas of 9-month-old white outbred rats under experimental alcohol intoxication versus a control group.